2003
DOI: 10.1046/j.1469-8137.2003.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Verne Grant and evolutionary studies of Aquilegia

Abstract: SummaryOne of Verne Grant's lasting contributions to plant evolutionary biology has been the recognition that differences between plants in floral characters can have a dramatic impact on both pollinator visitation and pollen transfer and thus affect reproductive isolation between nascent plant species (collectively, floral isolation). Here we review some of the concepts and findings from Grant's work on floral isolation, particularly with respect to the genus Aquilegia (Ranunculaceae). It has now been over 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 51 publications
1
84
0
2
Order By: Relevance
“…Numerous historical genetic studies on species of Aquilegia suggest that some characters separating species are controlled, at least in part, by genes of large effect, while other characters are controlled by many genes of small effect (Hodges et al, 2003). However, with the exception of inheritance studies of flower orientation, flower color and spur length (Hodges et al, 2002), no data are available that show a direct association between quantitative traits and molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous historical genetic studies on species of Aquilegia suggest that some characters separating species are controlled, at least in part, by genes of large effect, while other characters are controlled by many genes of small effect (Hodges et al, 2003). However, with the exception of inheritance studies of flower orientation, flower color and spur length (Hodges et al, 2002), no data are available that show a direct association between quantitative traits and molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between plants and pollinators -including co-evolution, pollinator sensory bias and associative learning (Schiestl and Johnson, 2013) -is particularly important for closely related floral species whose reproductive isolation is mediated by differential pollinator preference (Fulton and Hodges, 1999;Schemske and Bradshaw, 1999;Ramsey et al, 2003;Hodges et al, 2004;Aldridge and Campbell, 2007;Klahre et al, 2011). In many such cases the composition and class of volatiles in the scents overlap (Jürgens, 2004;Svensson et al, 2006;Waelti et al, 2008;Steiner et al, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…In Aquilegia, punctuated evolution of longer spur lengths correlates with shifts to pollinators possessing longer tongues [5,6]. Early hypotheses suggested that these spurs are produced by the activity of 'meristematic knobs' flanking the petal attachment point [7,8].…”
Section: Introductionmentioning
confidence: 99%